Until the end of time [compact disc, unabridged] : a novel - Steel, Danielle (Brilliance Audio, 2012)
Jenny and Bill are a married couple whose love is absolute. They're certain they're fated to be together until the end of time, but tragedy strikes when they least expect it, cutting their lives and their happiness short. More than thirty years later, Bob, a hardened New York City publisher, will meet his match in Lillibet, a shy Amish girl who is a talented writer. Though these two couldn't be less alike, they immediately sense a deep connection that spans their differences. And there's the unshakable sense that they've known each other for a long time, possibly in another life.